2012
DOI: 10.1186/1742-4690-9-20
|View full text |Cite
|
Sign up to set email alerts
|

Independent evolution of macrophage-tropism and increased charge between HIV-1 R5 envelopes present in brain and immune tissue

Abstract: BackgroundTransmitted HIV-1 clade B or C R5 viruses have been reported to infect macrophages inefficiently, while other studies have described R5 viruses in late disease with either an enhanced macrophage-tropism or carrying envelopes with an increased positive charge and fitness. In contrast, our previous data suggested that viruses carrying non-macrophage-tropic R5 envelopes were still predominant in immune tissue of AIDS patients. To further investigate the tropism and charge of HIV-1 viruses in late diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
58
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 86 publications
(135 reference statements)
4
58
2
Order By: Relevance
“…1a). Previous studies have reported that M-tropic variants are also more sensitive to sCD4 than T-tropic variants (27)(28)(29). We confirmed this observation by showing that M-tropic variants were on average 27-fold more sensitive to sCD4 than their T-tropic counterparts (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…1a). Previous studies have reported that M-tropic variants are also more sensitive to sCD4 than T-tropic variants (27)(28)(29). We confirmed this observation by showing that M-tropic variants were on average 27-fold more sensitive to sCD4 than their T-tropic counterparts (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Differences in how macrophage tropism is defined can lead to substantially different observations about M-tropic viruses. Although it is widely observed that M-tropic viruses are able to enter more efficiently at low CD4 densities (14,19,(22)(23)(24)(25)(26) and are more sensitive to neutralization by soluble CD4 (sCD4) (27)(28)(29) than T-tropic viruses, few other characteristics are widely agreed upon. Similarly, several amino acid changes in the HIV-1 Env protein have been associated with macrophage tropism (24,25,27,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), but the changes are not consistent across different subjects when macrophage tropism is defined as a distinct set of evolutionary variants within that subject (40).…”
mentioning
confidence: 99%
“…We confirmed the role of N283 in macrophage-tropic Env (12,37). However, the identification of many macrophage-tropic Envs that lack N283 (and non-macrophagetropic Envs with N283) indicates that other determinants play a significant role (13,19). We identified complex determinants that included residues on the N-terminal flank of the CD4 binding loop as well as changes in the glycan shield that may affect the exposure of CD4 contact residues (37,38).…”
supporting
confidence: 57%
“…Where possible, we included groups of Envs that had been amplified from single individuals and that included both macrophage-tropic and non-macrophage-tropic Envs. Mainly, we used a panel of Envs that we had previously studied (11) and included more recently amplified and characterized Envs (19 rions were titrated on HeLa TZM-BL cells, which carry ␤-galactosidase and luciferase reporter genes controlled by HIV long terminal repeat (LTR) promoters (46). Infected cells were visualized at 48 h after infection as focus-forming units (FFU) following staining for ␤-galactosidase activity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation